Difunctional electrocatalyst as well as preparation method and application thereof
By using a bifunctional electrocatalyst supported by niobium-doped titanium dioxide composite support in an acidic environment, the problem of insufficient catalytic efficiency and stability in the prior art is solved, and efficient and stable electrolytic water catalysis and efficient utilization of precious metals are achieved.
Patent Information
- Application Number
- CN202411561154.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The prior art lacks efficient and stable dual-function electrocatalysts in acidic environments, resulting in insufficient catalytic efficiency and stability of electrolyzed water.
Niobium-doped titanium dioxide composite is used as a support to support iridium nanoparticles, and the conductivity and dispersion of the catalyst are improved through specific preparation methods, thereby enhancing the catalytic activity and stability of OER and HER.
It realizes efficient catalytic electrolysis of water in an acidic environment, improves catalytic stability and utilization of iridium precious metals, and reduces the cost of the catalyst.
Smart Images

Figure CN119506945A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a bifunctional electrocatalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has the advantages of high energy density, clean and environmentally friendly, and wide application. It is a promising alternative energy source. Water electrolysis is an effective way to produce green hydrogen sustainably. Compared with alkaline electrolyzers, proton exchange membrane electrolysis (PEMWE) has the advantages of low resistance loss, high electrolyzer efficiency, high current density, and fast response speed. It is considered to be the most promising hydrogen production technology. However, the high cost of proton exchange membrane (PEM) limits its further application, so it is urgent to reduce the cost of the stack and improve the efficiency of the catalyst by optimizing the design of the catalyst, thereby promoting large-scale application.
[0003] At present, the anode is the main factor affecting the application of water electrolysis due to its relatively slow kinetics and high overpotential. In the PEM electrolyzer, the oxygen evolution reaction (OER) catalyst is composed of the precious metal Ru with low overpotential. However, due to the instability of Ru, it is easy to dissolve in the acidic electrolyte, and the amount of precious metal is high, the utilization rate is low, the catalytic efficiency is low and the activity is unstable; secondly, the OER and HER electrocatalysts synthesized separately for different equipment and processes have high costs. Related technologies have developed bifunctional electrocatalysts with high OER and HER activities, such as NiSe, Ni 2 P, CoMnO, etc., but these bifunctional catalysts are all used in alkaline overall water decomposition, and there is still a lack of bifunctional electrocatalysts in acidic solutions.
[0004] Therefore, it is necessary to provide a bifunctional electrocatalyst to improve its catalytic efficiency and stability in water electrolysis in an acidic environment. Summary of the invention
[0005] In view of this, the present application provides a bifunctional electrocatalyst and a preparation method and application thereof, which are used to solve the problem of how to improve the catalytic efficiency and stability of the bifunctional electrocatalyst in the electrolysis of water in an acidic environment.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a bifunctional electrocatalyst, which includes a carrier and iridium nanoparticles loaded on the carrier, wherein the carrier is a niobium-doped titanium dioxide composite.
[0007] In a second aspect, the present application provides a method for preparing a bifunctional electrocatalyst, comprising the following steps: S1. The titanium-containing organic matter and the niobium-containing compound are added to an acidic solution containing polyethyleneimine, stirred, heated to react, and then dried to obtain a niobium-doped titanium dioxide composite; S2. A solution containing an iridium compound is dropped into the dispersion of the niobium-doped titanium dioxide composite, and the mixture is subjected to gradient heating reaction. After washing and drying, a bifunctional electrocatalyst is obtained.
[0008] Preferably, in step S1, the stirring temperature is 20-40°C, and the stirring time is 3-5h; the heating reaction temperature is 95-105°C, and the heating reaction time is 24-28h.
[0009] Preferably, in step S2, the gradient heating reaction process is: stirring at 70-90° C. for 4-6 h, stirring at 140-160° C. for 4-6 h.
[0010] Preferably, in step S1, the titanium-containing organic matter includes one or more of isopropyl titanate and titanium tetrachloride; the niobium-containing compound includes one or more of niobium pentachloride and niobium ethoxide; and the acidic solution containing polyethyleneimine includes a mixture of polyethyleneimine, glacial acetic acid and water.
[0011] Preferably, in step S2, the iridium-containing compound includes one or more of chloroiridic acid and iridium trichloride; the solvent of the dispersion of the niobium-doped titanium dioxide composite includes one or more of ionized water, ethanol and isopropanol; and the solvent of the solution of the iridium compound includes isopropanol.
[0012] Preferably, the molar ratio of the titanium-containing organic matter to the niobium-containing compound is 19:1-3 based on metal ions; and the amount of polyethyleneimine used is 1.5 g.
[0013] Preferably, the molar ratio of the iridium-containing compound to the niobium-doped titanium dioxide composite is 0.214-2.136:1, calculated as metal ions.
[0014] In a third aspect, the present application provides an application of a bifunctional electrocatalyst in the field of water electrolysis.
[0015] Preferably, the hydrolysis system for water electrolysis is an acidic system. The beneficial effects of the present application are as follows: the present application uses niobium-doped titanium dioxide as a carrier to prevent electrochemical oxidation corrosion and improve the catalytic stability; at the same time, doping niobium in the carrier improves the conductivity of the carrier, which is conducive to better dispersion and anchoring of iridium precious metal, improves the catalytic activity and stability of OER and HER in an acidic environment, and the utilization rate of iridium precious metal is high.
[0016] In this application, the characteristic of polymer polyethyleneimine that it can be oriented and self-assembled is utilized to successfully prepare a niobium-doped titanium dioxide carrier, while increasing the specific surface area of the niobium-doped titanium dioxide carrier, providing more binding sites for the iridium precious metal to the niobium-doped titanium dioxide carrier, thereby improving the catalytic activity of OER and HER and the utilization rate of the iridium precious metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the XRD pattern of the niobium-doped titanium dioxide-supported iridium nanoparticle catalyst prepared in Example 1 of the present invention; Figure 2 and Figure 3 This is a TEM image of the niobium-doped titanium dioxide-supported iridium nanoparticle catalyst prepared in Example 4 of the present invention; Figure 4 Polarization curves of the catalysts obtained in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention under OER; Figure 5 Polarization curves of the catalysts obtained in Example 4, Comparative Example 1 and Comparative Example 3 under HER; Figure 6 The chronoamperometry diagrams of the catalysts obtained in Example 4 of the present invention and Comparative Example 1 under OER; Figure 7 The chronoamperographs of the catalysts obtained in Example 1 of the present invention and Comparative Example 3 under HER. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The present application provides a bifunctional electrocatalyst, which includes a carrier and iridium nanoparticles loaded on the carrier, wherein the carrier is a niobium-doped titanium dioxide composite.
[0020] The bifunctional electrocatalyst of the present application is a niobium-doped titanium dioxide-supported iridium nanoparticle catalyst, which has high OER and HER catalytic activity in an acidic system and high catalytic stability. The reason is that, on the one hand, niobium-doped titanium dioxide as a carrier can prevent electrochemical oxidation corrosion to improve catalytic stability; on the other hand, niobium doped in the carrier can improve the conductivity of the carrier, which is conducive to better dispersion and anchoring of iridium precious metals, improve the catalytic activity and stability of OER and HER, and the utilization rate of iridium precious metals is high to reduce the cost of the catalyst.
[0021] The present application provides a method for preparing a bifunctional electrocatalyst, comprising the following steps: S1. The titanium-containing organic matter and the niobium-containing compound are added to an acidic solution containing polyethyleneimine, stirred, heated to react, and then dried to obtain a niobium-doped titanium dioxide composite; S2. A solution containing an iridium compound is dropped into the dispersion of the niobium-doped titanium dioxide composite, and the mixture is subjected to gradient heating reaction. After washing and drying, a bifunctional electrocatalyst is obtained.
[0022] In the present application, the characteristic of polymer polyethyleneimine that it can be oriented and self-assembled is utilized to successfully prepare a niobium-doped titanium dioxide carrier, while increasing the specific surface area of the niobium-doped titanium dioxide carrier, providing more binding sites for the iridium precious metal to the niobium-doped titanium dioxide carrier, thereby improving the catalytic activity of OER and HER and the utilization rate of the iridium precious metal.
[0023] In some embodiments, in step S1, the stirring temperature is 20-40°C, and the stirring time is 3-5h; the heating reaction temperature is 95-105°C, and the heating reaction time is 24-28h, and the heating reaction vessel is a high-pressure reactor.
[0024] In some embodiments, in step S2, the process of gradient heating reaction is: stirring at 70-90° C. for 4-6 hours, stirring at 140-160° C. for 4-6 hours, and the vessel for gradient heating reaction is a high-pressure reactor.
[0025] In some embodiments, in step S1, the titanium-containing organic matter includes one or more of isopropyl titanate and titanium tetrachloride; the niobium-containing compound includes one or more of niobium pentachloride and niobium ethoxide; and the acidic solution containing polyethyleneimine includes a mixture of polyethyleneimine, glacial acetic acid, and water.
[0026] In some embodiments, in step S2, the iridium-containing compound includes one or more of chloroiridic acid and iridium trichloride; the solvent of the dispersion of the niobium-doped titanium dioxide composite includes one or more of ionized water, ethanol, and isopropanol; and the solvent of the solution of the iridium compound includes isopropanol.
[0027] In some embodiments, the molar ratio of the titanium-containing organic compound to the niobium-containing compound is 19:1-3 based on metal ions; and the amount of polyethyleneimine used is 1.5 g.
[0028] In some embodiments, the molar ratio of the iridium-containing compound to the niobium-doped titanium dioxide composite is 0.214-2.136: 1, calculated as metal ions. Under this condition, the iridium loading (ratio of the mass of Ir in the iridium compound to the mass of the carrier) in the obtained niobium-doped titanium dioxide-supported iridium nanoparticle catalyst (Ir / NTO) is 0.5: 1-5: 1.
[0029] The present application provides an application of a bifunctional electrocatalyst in the field of water electrolysis, including but not limited to application as an anode catalyst for water electrolysis, a cathode catalyst for water electrolysis, and full-cell water electrolysis. In the full-cell water electrolysis process, the anode catalyst layer and the cathode catalyst layer contain niobium-doped titanium dioxide-loaded iridium nanoparticle catalysts.
[0030] In the present application, the hydrolysis system for water electrolysis is an acidic system.
[0031] The present solution is further described below through specific embodiments.
[0032] Example 1 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of isopropyl titanate and 1.256g of niobium pentachloride and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.2g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 15.6mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 3.205ml of iridium compound-containing solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h to obtain the product Ir / NTO, and the mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 1:1.
[0033] Example 2 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 1.802g of titanium tetrachloride and 1.256g of niobium pentachloride and add them to solution A. After continuous stirring for 2h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.2g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 15.6mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 3.205ml of iridium compound-containing solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 5h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h to obtain the product Ir / NTO, the mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 1:1.
[0034] Example 3 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of isopropyl titanate and 1.478g of niobium ethanol and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.1g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 15.6mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:9:0) to obtain a dispersion of niobium-doped titanium dioxide composite; add 1.603ml of iridium compound-containing solution to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h to obtain the product Ir / NTO, the mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 0.5:1.
[0035] Example 4 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of isopropyl titanate and 1.256g of niobium pentachloride and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.4g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 31.2mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 3.205ml of iridium compound solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h, and obtain the product Ir / NTO. The mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 2:1.
[0036] Example 5 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of titanium tetrachloride and 1.478g of niobium ethanol and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.5g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 31.2mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 4.808ml of iridium compound solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h, and obtain the product Ir / NTO. The mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 3:1.
[0037] Example 6 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of titanium tetrachloride and 1.256g of niobium pentachloride and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.6g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 46.8mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 4.274ml of iridium compound-containing solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h, and obtain the product Ir / NTO. The mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 4:1.
[0038] Example 7 A method for preparing a bifunctional electrocatalyst comprises the following steps: S1. Drop 1.5g of polyethyleneimine into a mixed solution consisting of 30ml of deionized water and 1.5ml of glacial acetic acid, and stir at room temperature for 30min to obtain solution A. Then take 3ml of titanium tetrachloride and 1.478g of niobium ethanol and add them to solution A. After continuous stirring for 3h, transfer the obtained colloidal suspension to a 100ml autoclave, react at 100℃ for 24h, wash the obtained powder by centrifugation with deionized water for 3 times, and then place the powder in a vacuum drying oven and dry it at 80℃ for 12h to obtain a niobium-doped titanium dioxide composite, which is a niobium-doped titanium dioxide carrier; S2. Weigh 0.7g of chloroiridic acid compound (Ir = 39wt%) and drop it into isopropanol (Ir concentration is 46.8mg / mL), stir at room temperature to obtain a uniform solution, that is, a solution containing iridium compound, disperse 50mg of niobium-doped titanium dioxide carrier in 50ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) to obtain a dispersion of niobium-doped titanium dioxide composite; add 5.342ml of iridium compound solution dropwise to the dispersion of niobium-doped titanium dioxide composite, heat to 80℃ in a water bath and continue stirring for 6h, then transfer to a high-pressure reactor and react at 150℃ for 5h. Then, wash alternately with ethanol and deionized water by centrifugation 4 times, put the obtained sample into a vacuum drying oven, dry at 90℃ for 12h, and obtain the product Ir / NTO. The mass ratio of iridium nanoparticles to niobium-doped titanium dioxide carrier is 5:1.
[0039] Comparative Example 1 A method for preparing an electrocatalyst comprises the following steps: Weigh 0.3 g of iridium chloride compound (Ir = 39 wt%) and drop it into isopropanol (Ir concentration is 15.6 mg / mL), and stir at room temperature to obtain a uniform solution. Prepare 50 ml of solvent (deionized water: ethanol: isopropanol = 1:8:1) and record it as solution B. Take 5.342 ml of iridium chloride solution prepared in step (1) into solution B, heat it to 80 ° C in a water bath and continue stirring for 6 h, then transfer it to a high-pressure reactor and react at 150 ° C for 5 h. Then, wash it with ethanol and deionized water alternately by centrifugation for 4 times, and put the obtained sample into a vacuum drying oven and dry it at 90 ° C for 12 h to obtain the product self-prepared Ir nanoparticles (SP Ir NP).
[0040] Comparative Example 2 Commercial iridium oxide catalyst, produced by McLean Company.
[0041] Comparative Example 3 Commercial platinum-carbon catalyst, manufactured by Aladdin.
[0042] Comparative Example 4 A method for preparing an electrocatalyst, the other contents of which are the same as those of Example 1, except that the chloroiridic acid compound is replaced with an equal mass of water.
[0043] Comparative Example 5 A method for preparing an electrocatalyst, the other contents of which are the same as those of Example 1, except that niobium pentachloride is replaced with an equal mass of isopropyl titanate.
[0044] Test and Evaluation The polarity performance of the obtained electrocatalyst was tested using an electrochemical workstation model of CHI660e. A three-electrode system was used, with a saturated calomel electrode as the reference electrode, a high-purity graphite carbon electrode as the counter electrode, and a glassy carbon electrode as the working electrode. The electrolyte used was 0.5 M H 2 SO 4 Solution. Weigh 5 mg of each catalyst into a centrifuge tube, add 100 μL of deionized water, 375 μL of ethanol and 25 μL of 5 wt% Nafion solution (perfluorosulfonic acid polymer solution) in sequence. Put the mixed solution into an ultrasonic crusher and ultrasonicate it in an ice bath for 30 minutes to obtain ink. Take 1.8 μL of the ink drop and apply it on a glassy carbon electrode with a diameter of 3 mm. After natural drying, the working electrode is obtained.
[0045] (1) For oxygen evolution reaction, before testing, the electrode was activated in the range of 1.1-1.5 V (vs. RHE) until the curve reached a stable state. The scanning range of the CV curve was 0-1.4 V (vs. RHE) and the scanning rate was 50 mV s -1The scanning range of the linear polarization curve is 1.1~1.7V (vs.RHE) and the scanning rate is 5mV s -1 ; 0~1.4V (vs.RHE), scan rate 50mV s -1 The electrochemical impedance spectroscopy (EIS) test was carried out at a constant voltage of 1.55 V (vs. RHE) and a frequency range of 0.1 Hz to 106 Hz. The stability test was carried out using the chronopotentiometry (CP) test at a constant current density of 10 mA cm -2 The stability of the material was tested and the results are shown in Table 1.
[0046] Table 1 Oxygen evolution reaction test results
[0047] (2) For the hydrogen evolution reaction, before testing, the electrode was activated in the range of 0.2~-0.3V (vs.RHE) until the curve reached a stable state. The scanning range of the linear polarization curve was 0.2~-0.3V (vs.RHE) and the scanning rate was 5mV s -1 The electrochemical impedance spectroscopy (EIS) test was carried out at a constant voltage of -0.29 V (vs. RHE) and a frequency range of 0.1 Hz to 106 Hz. The stability test was carried out using the chronopotentiometry (CP) test at a constant current density of -10 mA cm -2 The stability of the material was tested and the results are shown in Table 2.
[0048] Table 2 Hydrogen evolution reaction test results
[0049] Table 1 and Table 2 are the performance of the embodiments and comparative examples under OER and HER tests. It can be seen that the oxygen evolution overpotential of the embodiment is significantly less than that of the comparative example, indicating that a higher current density can be obtained at a lower voltage. The smaller the Tafel slope and Rct, the better the catalytic performance. And in terms of mass activity, it can be seen that the embodiment has a higher mass activity, indicating that the utilization rate of the precious metals in the embodiment is higher.
[0050] The X-ray diffraction (XRD) test method is: take a small amount of powder for testing, the test angle range is 10-80°, and the scanning speed is 3° / min. The high-resolution transmission electron microscope (HRTEM) test method is: take a small amount of powder and disperse it in ethanol solvent, take a drop of liquid and drop it on the ultra-thin carbon film grid, and perform HRTEM test after the liquid evaporates. Figure 1 This is the XRD pattern of the niobium-doped titanium dioxide-supported iridium nanoparticle catalyst prepared in Example 1; Figure 1It can be seen that the niobium-doped titanium dioxide-supported iridium nanoparticle catalyst synthesized by the present invention has obvious diffraction peaks at 2θ=25.26°, 37.73°, 48.11°, 53.78°, 55.11°, and 62.43°, which belong to the anatase structure and no obvious diffraction peaks of niobium compounds are seen. There are obvious diffraction peaks at 2θ=41.09° and 47.37°, which belong to the iridium metal structure.
[0051] Figure 2 and Figure 3 TEM image of niobium-doped titanium dioxide-supported iridium nanoparticle catalyst prepared in Example 4 of the present invention; Figure 2-3 It can be seen that the iridium metal nanoparticles are uniformly dispersed on the niobium-doped titanium dioxide carrier, and the lattice fringes of the niobium-doped titanium dioxide carrier and the metal iridium nanoparticles can be clearly seen, and the values are consistent with XRD.
[0052] Figure 4 Polarization curves of the catalysts obtained in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention under OER; Figure 5 Polarization curves of the catalysts obtained in Example 4, Comparative Example 1 and Comparative Example 3 under HER; Figure 6 The chronoamperometry diagrams of the catalysts obtained in Example 4 of the present invention and Comparative Example 1 under OER; Figure 7 The chronoamperometric diagrams of the catalysts obtained in Example 1 and Comparative Example 3 under HER conditions are shown in FIG. Figure 4-7 It can be seen that Example 1 and Example 4 prepared using the present invention have excellent catalytic efficiency in both oxygen evolution reaction and hydrogen evolution reaction, and are better than the catalysts in the comparative examples; in terms of stability, it can also be seen that the stability performance of the niobium-doped titanium dioxide-supported iridium nanoparticle catalyst synthesized by the present invention is better than that of the catalyst in the comparative example.
[0053] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A bifunctional electrocatalyst, characterized in that: The invention comprises a carrier and iridium nanoparticles loaded on the carrier, wherein the carrier is a niobium-doped titanium dioxide composite.
2. A method for preparing a bifunctional electrocatalyst as claimed in claim 1, characterized in that: The following steps are involved: S1. The titanium-containing organic matter and the niobium-containing compound are added to an acidic solution containing polyethyleneimine, stirred, heated to react, and then dried to obtain a niobium-doped titanium dioxide composite; S2. A solution containing an iridium compound is dropped into the dispersion of the niobium-doped titanium dioxide composite, and the mixture is subjected to gradient heating reaction. After washing and drying, a bifunctional electrocatalyst is obtained.
3. The preparation method according to claim 2, characterized in that In step S1, the stirring temperature is 20-40°C, and the stirring time is 3-5 hours; the heating reaction temperature is 95-105°C, and the heating reaction time is 24-28 hours.
4. The preparation method according to claim 2, characterized in that In step S2, the gradient heating reaction process is: stirring at 70-90° C. for 4-6 h, stirring at 140-160° C. for 4-6 h.
5. The preparation method according to claim 2, characterized in that In step S1, the titanium-containing organic matter includes one or more of isopropyl titanate and titanium tetrachloride; the niobium-containing compound includes one or more of niobium pentachloride and niobium ethoxide; and the acidic solution containing polyethyleneimine includes a mixture of polyethyleneimine, glacial acetic acid and water.
6. The preparation method according to claim 2, characterized in that In step S2, the iridium-containing compound includes one or more of chloroiridic acid and iridium trichloride; the solvent of the dispersion of the niobium-doped titanium dioxide composite includes one or more of ionized water, ethanol, and isopropanol; and the solvent of the solution of the iridium compound includes isopropanol.
7. The preparation method according to claim 2, characterized in that Calculated on the basis of metal ions, the molar ratio of the titanium-containing organic matter to the niobium-containing compound is 19:1-3.
8. The preparation method according to claim 2, characterized in that The molar ratio of the iridium-containing compound to the niobium-doped titanium dioxide composite is 0.214-2.136:1 based on metal ions.
9. Use of a bifunctional electrocatalyst obtained by the preparation method according to any one of claims 2 to 8 in the field of water electrolysis.
10. The use according to claim 9, characterized in that The hydrolysis system for water electrolysis is an acidic system.
Citation Information
Patent Citations
Titanium dioxide supported iridium catalyst as well as preparation method and application thereof
CN117165998A
Iridium catalyst taking niobium-doped titanium oxide as carrier as well as preparation method and application of iridium catalyst
CN117904664A
Iridium catalyst based on heterostructure carrier as well as preparation method and application of iridium catalyst
CN118166393A